2003
DOI: 10.1021/ja0291181
|View full text |Cite
|
Sign up to set email alerts
|

First X-ray Characterization and Theoretical Study of π-Alkyne, Alkynyl-Hydride, and Vinylidene Isomers for the Same Transition Metal Fragment [Cp*Ru(PEt3)2]+

Abstract: The reaction of the chloro-complex [CpRuCl(PEt(3))(2)] with acetylene gas in methanol gave the pi-alkyne complex [CpRu(eta(2)-HCtbd1;CH)(PEt(3))(2)][BPh(4)] (1), which has been structurally characterized by X-ray analysis. The alkyne complex undergoes spontaneous isomerization even at low temperature, yielding the metastable alkynyl-hydride complex [CpRu(H)(Ctbd1;CH)(PEt(3))(2)][BPh(4)] (2), as the result of the oxidative addition of the alkyne C-H bond. This compound has also been structurally characterized d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 50 publications
7
72
0
1
Order By: Relevance
“…[60,61] The interaction energy at the hydride site remains almost unchanged, showing that the electronic effect of the phenyl substituents is also small. The results at the metal site contrast with those at the hydride site.…”
Section: Full Papermentioning
confidence: 87%
“…[60,61] The interaction energy at the hydride site remains almost unchanged, showing that the electronic effect of the phenyl substituents is also small. The results at the metal site contrast with those at the hydride site.…”
Section: Full Papermentioning
confidence: 87%
“…[10,29,82] With the exception of the reaction with HCl, the amine complexes [(C 5 system for computation using a combination of DFT and quantum mechanics/molecular mechanics calculations. [97] Whereas the solid-state structures determined by X-ray crystallography for several alkynyl hydrido complexes show a transoid disposition of alkynyl and hydrido ligands (Figure 18 SO 3 ]. This compound is stabilized by means of an agostic interaction with a hydrogen atom of one of the isopropyl groups of the TpiPr ligand, as revealed by X-ray crystallography [ Figure 19; Ru···C(H agostic ) 2.627(6) Å , Ru···H agostic 1.83(6) Å ].…”
Section: Ruthenium Complexesmentioning
confidence: 99%
“…[2,[20][21][22] To rationalize the alternative pathways, several theoretical studies have been carried out, [23][24][25][26] and recent experimental and theoretical studies have demonstrated that a bimolecular mode for the h 2 -alkyne-h 1 -vinylidene isomerization process was also possible. [27,28] Vinylidenes can also be produced from ruthenium hydride complexes by insertion of the triple bond to form a vinyl ruthenium species followed by a-H migration.…”
Section: Introductionmentioning
confidence: 99%